Islamic School Promotion Through Multicultural Education Curriculum Integration at As-Salam Day School, North America - Aniq, Ahmad Fathan (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2024)
This study aims to uncover the promotion strategies carried out by teachers and school leaders of as-Salam Day School in America through moderation-based multicultural education. This Islamic school was able to get the best praise with double accreditation. This achievement answers the accusation that Islam is harsh and unable to compete in America. As-Salam Islamic School integrates Islamic achievements and teachings into an independent curriculum. Using qualitative research methods, this research was approached institutionally. Data were obtained from document study in the form of reports. The research findings illustrate that first, the main curriculum implemented by As-Salam Day School is based on academic achievement and strengthening multiculturalist religious identity. Second, As-Salam Day School's curriculum integration integrates various cultural and religious backgrounds, both Muslim and non-Muslim. Third, the Islamic school's promotional strategy is carried out at community celebrations involving parents, alumni, and the wider community, which aims to promote intercultural dialogue and strengthen the relationship between the school and the community. The school also embraces inclusive youth and parents who want to learn Islam.